FISH FAUNA OF KAMTHIKHAIRY DAM IN PENCH NATIONAL PARK, MAHARASHTRA - Swapmil s. Ghatget; Sachin W. Belsare; Shrikant S. Jadhav (Journal of Indian Fisheries Association, 2018)
We studied the fish fauna of Kamthikhairy dam for two years (March, 2013 to February, 2015) and recorded 34 fish species belonging to 6 orders 13 families and 26 genera. Cypriniformes was the dominant order reprosented by 16 species, followed by Perciformes (9 species). SHurifomies (6 species) while Synbranchiformes, Beloniformes andOsteoglossitores were represented by 1 species each. Of the 34 fish species, 3 belong to Near Threatened (NT) and rest 21 to the Least Concern (LC) category for IUCN Red List criteria. The present study reports 20 new records of indigenous (12 species) and introduced (8 species) in Pench National Park, respectively. A number of species based on previous study and the current study adds to the total of 53 fish species in the waterbodies of Pench National Park.